Penguin Film Periapikal Gigi untuk Pemotretan Sendi Rahang dengan Alat Bantu Condy Ray - Heru Suryonegoro (Faculty of Dentistry, Universitas Indonesia, 2015)
The projection that often used for assessing the temporomandibular joint is transcranio-lateral oblique or Schueller projection. This projection still cannot provide the excellent image, since film size used in this projection (10 cm x 15 cm) is too large compare to that of the temporomandibular joint image size which around 3 cm square. Also, economically the use of large film size is not efficient, as well as it will cause overlapping of the joint image with the surrounding anatomical structure that obscure the detail image and leads to misinterpretation. Transcranio-lateral Oblique projection with the aid of "Condy Ray" seems to resolve the problem of using large film, since it is enable to use small size (3 cm x 4 cm) of extra oral film, focusing the image of temporomandibular joint. The purpose of this research using the dental periapical film for temporo mandibular joint projetion, is to overcome the high cost problem as well as avoiding the obscure image.